Phylogenomics of Allium section Cepa (Amaryllidaceae) provides new insights on domestication of onion - Yusupov, Ziyoviddin (Plant Divers, 2020)
Allium sect. Cepa (Amaryllidaceae) comprises economically important plants, yet resolving the phylogenetic relationships within the section has been difficult as nuclear and chloroplast-based phylogenetic trees have been incongruent. Until now, phylogenetic studies of the section have been based on a few genes. In this study, we sequenced the complete chloroplast genome (plastomes) of four central Asian species of sect. Cepa: Allium oschaninii, A. praemixtum, A. pskemense and A. galanthum. Their chloroplast (cp) genomes included 114 unique genes of which 80 coded proteins. Seven protein-coding genes were highly variable and therefore promising for future phylogenetic and phylogeographic studies. Our plastome-based phylogenetic tree of Allium sect. Cepa revealed two separate clades: one comprising the central Asian species A. oschaninii, A. praemixtum, and A. pskemense, and another comprising A. galanthum, A. altaicum, and two cultivated species, A. cepa and A. fistulosum. These findings contradict previously reported phylogenies that relied on ITS and morphology. Possible explanations for this discrepancy are related to interspecific hybridization of species ancestral to A. galanthum and A. cepa followed by chloroplast capture; however, this is impossible to prove without additional data. Our results suggest that the central Asian Allium species did not play a role in the domestication of the common onion. Among the chloroplast genes, rpoC2 was identified as a gene of choice in further phylogeographical studies of the genus Allium.